Iodixanol versus iopromide in patients with renal insufficiency undergoing coronary angiography with or without PCI. Issue 18 (May 2018) - Zhang, Junyi; Jiang, Yufeng; Rui, Qing; Chen, Min; Zhang, Nannan; Yang, Huajia; Zhou, Yafeng
Abstract: Background: The use of contrast agents during coronary angiography can result in contrast-induced nephropathy (CIN), particularly in patients with renal dysfunction. On the contrary, different contrast agents can induce different degree of changes in cardiac function. The objective of our meta-analysis was to compare the clinical safety of iso-osmolar contrast medium iodixanol to low-osmolar contrast medium iopromide in patients with renal insufficiency undergoing coronary angiography with or without percutaneous coronary intervention (PCI). Methods: We searched Medline, Embase, Cochrane Library, and reference lists to identify randomized controlled trials that compared iodixanol to iopromide with the incidence of CIN as an endpoint in renal impaired patients undergoing coronary angiography. Outcome measures were the incidence of CIN, absolute peak serum creatinine (Scr) increase from baseline and a composite of cardiovascular adverse events. Results: A total of 8 trials with 3532 patients were pooled; 1759 patients received iodixanol and 1773 patients received iopromide. There was no significant difference in the incidence of CIN (summary odds ratio [OR] 0.50, 95% confidence interval [CI] 0.19–1.35, P  = .17) and peak Scr increase (mean difference −0.01 mg/dL, 95% CI −0.08 to 0.05, P  = .69) when iodixanol was compared with iopromide. But iodixanol was associated with a statistically significant reduction in cardiovascular adverse events when compared with iopromide (OR 0.47, 95% CI 0.30–0.73, P  = .0009). Conclusions: Analysis of pooled data from 8 randomized controlled trials of iodixanol against iopromide in patients with renal insufficiency undergoing coronary angiography with or without PCI showed that iodixanol nonsignificantly reduced the incidence of CIN, but was associated with a significantly reduced risk of cardiovascular adverse events when compared with iopromide.